Judicial creativity in the Malaysian Shari'ah (Syariah)Courts : the need for paradigm shift - Mohd Zin, Najibah (American-Eurasian Network for Scientific Information (AENSI), Jordan, 2011)
Judicial creativity helps develop law by way of ijtihad. This fact has been proven in various fields of the Shari‘ah. The paper discusses some of these areas and concludes that with the added contribution of qadhis, the Shari‘ah is equally relevant in all spheres of human relations (muamalat) and can solve any socio-legal problem in times to come.